Benefits of a programme taking advantage of patient-instructors to teach and assess musculoskeletal skills in medical students. Issue 12 (17th May 2006) - Bideau, M; Guerne, P-A; Bianchi, M-P; Huber, P
Abstract : Aim: To evaluate a rheumatoid arthritis patient-instructor-based formation–assessment programme for its ability to improve and assess musculoskeletal knowledge and skills in third-year medical students. Methods: (1) The quality of our musculoskeletal teaching was assessed before patient-instructor intervention through an open-questions test (pre-test) and performance record forms (PRFs) filled in by the patient-instructors. (2) The improvement afforded by patient-instructors was evaluated through a second (identical) open-questions test (post-test). (3) The resulting skills in the students were further assessed by an individual patient-instructors physical status record form (PSRF), filled in by the students. Results: Pre-tests and post-tests showed an improvement in correct answers from a mean score of 39% to 47%. The history-taking questions that obtained <50% scores in the pre-test mostly dealt with the consequences of a chronic illness. Intervention of patient-instructors especially improved knowledge of the psychosocial aspects and side effects of drugs. With regard to physical examination, patient-instructors makedly improved the identification of assessment of signs of active and chronic inflammation. PRF analysis showed that 10 of 28 questions answered by <50% of the students were related to disease characteristics of rheumatoid arthritis, extra-articular signs, side effects of drugs and psychosocial aspects. Analysis of the PSRF indicated that the weakness of our students' physical examination abilities in particular is related to recognising the types of swelling and differentiating tenderness from pain on motion . Conclusion: This study proves the considerable benefits of the involvement of patient-instructors in the teaching and assessment of clinical skills in students.